Analysis of electrical energy audit for lighting on electrical engineering buildings Malikussaleh University - Siagian, Manutur JT; Multazam, Teuku; Nasution, Fakhruddin Ahmad (Journal Geuthee of Engineering and Energy, 2023)
The electrical engineering building at Malikussaleh University has a large enough need for electrical energy. Consumption of electrical energy in this building has increased from year to year which affects the amount of electric power and high operating costs. The main cause is the large number of lighting lamps that are used so that the impact on the high costs that must be paid to the PLN. Therefore, in this study an assessment will be carried out regarding the causes of not realizing the effective and efficient use of electrical energy. Energy audit is one of the methods used to find out in detail about the need for proportional energy consumption in accordance with the applicable Indonesian National Standards (SNI) so that it will provide comfort for users. The variables used in this audit are the compatibility between the light used in each available room, as well as the type of lamp material used. The calculation results show that the problem is the high consumption of electrical energy because a lot of electrical equipment is not environmentally friendly, which affects the costs incurred. The amount of energy or kWh that must be paid each year is Rp. 30,300,949.98